Effect of beetroot extract (beta vulgaris) against olanzapine on the pituitary, thyroid, and fertility in adult white male rats - Haleema Yousef ALNAHARY; Ghada L. TALEB; Naglaa Y. ABUZINADAH; Hanan Msaa AL JAMEI; Mariam ALGAMDI; Haneen Nasser AHMED; Hanan Abdulkarim SANGOUF; Anoud A. ALTHAGAFI (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Olanzapine (OLZ) is a second-generation atypical drug that is commonly used to treat schizophrenia. However, it is known to affect male sexual functions, reproductive processes, and spermatogenesis. This study aims to investigate the effectiveness of beetroot extract in reducing the side effects of Olanzapine. The study involved 46 male Wistar rats weighing 150-200 g, administered intraperitoneal doses of OLZ and beetroot extract at (10 mg/kg) daily for six weeks. Thyroid-stimulating hormone (TSH), triiodothyronine (T3), tetraiodothyronine (T4), (T3/T4), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone levels were measured. The study found that beetroot extract treatment significantly increased thyroidstimulating hormone levels by 81% and TSH by 82% in the third and sixth weeks, while Triiodothyronine levels decreased by 42% and thyroxin levels by 115% in the third and sixth weeks, also, there was a significant decrease in testosterone levels in the group treated with Olanzapine by 108 % in the third week and by 116% in the sixth week when compared to a control group; additionally, the study found a 25% increase in absolute body weight in the beetroot extract group and 26% increase in a combined group treated with Olanzapine compared to Olanzapine. Histological sections of the thyroid gland and testis were taken at the end of the sixth week. OLZ caused atrophy of follicular epithelium in the thyroid gland and shrunken seminiferous tubules, with disorganized germinal epithelium in the testis; however, beetroot extract treatment resulted in normal testicular histology, characterized by regular tubules with stratified germinal epithelium and Leydig cell clusters. However, some sperm aggregation was observed in the tubular luminae. It concluded that administrating beetroot extract (10 mg/kg) daily for six weeks significantly improved the pituitary, thyroid, and fertility in adult white male rats.